MARKETING ANALYSIS AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY GLOBAL COMPETITION ERA - Indra Sani; Wenny Desty Febrian (Jurnal Perspektif Manajerial dan Kewirausahaan (JPMK), 2023)
This scientific paper aims to provide an overview of existing scientific papers from a researcher's perspective. The method used as a discussion uses a graphic style of writing. Analysts collect necessary data from additional sources before the data can be properly analyzed and finalized. Information for the study will be collected using incremental data collection methods. Additional details are gleaned from books, articles, research papers, lecture notes, and the Internet. As part of the literature review, relevant scientific papers were selected, researched, and revised. The variables described in the Results and Discussion provide answers that are consistent with the purpose of this dissertation, which is an explanation by providing perspective, and then other variables that can be used as features, research subjects, and research outcome models. Continue. the findings in previous articles on marketing relate to customer loyalty Likewise, customer satisfaction is also related, several international articles sourced from Scopus publications, ScienceDirect, have very diverse influences between variables. The novelty in this scientific work is that variables have never been studied in marine transportation service companies.